PENGARUH PENERAPAN CASE BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI PENGETAHUAN DASAR GEOGRAFI - Dila, Apin; Nofrion, Nofrion (JURNAL BUANA, 2023)
This study aims to determine the effect of Case Based Learning learning model on student learning outcomes in the basic knowledge of geography. Which will be held at SMAN 1 Harau in the 2022/2023 academic year. This study uses a quasi-experimental method, with the type of research in the form of a posttest control only group design. As for the research sample using purposive sampling technique. The sample in this study was the X IPS 1 students who had 36 students as an experimental class, by applying the Case Based Learning model. While X IPS 5 which has 36 students as a conventional class, applies a scientific approach model. This study used data collection techniques in the form of written tests, 45 multiple choice questions and documentation tests. From the results of the average posttest value of the experimental class, it was obtained that the score was 83.61 and the conventional class was 61.69. Data analysis of the two sample groups used a t-test with the SPSS 21 system in order to obtain a significance of 0.00 which is below = 0.05 (sig>α). This means that there is a significant influence from the application of Case Based Learning on student learning outcomes in the basic knowledge of Geography.